Types of Personal Social Networks of Older Adults in Portugal - Guadalupe, Sónia (2020)
This study presents and discusses a three-dimensional typology for personal social networks of Portuguese older adults. We used a K-means cluster analysis of structural, functional and relational-contextual variables of the networks of 612 participants aged 65 + (M = 76 ± 7.6), mostly women (63%). Four types of networks emerged: family networks, friendship networks, neighbourhood networks and institutional networks. The most frequent are family networks (61.8%), constituted by 94.6% of family ties, on average, attesting the familistic nature of the older persons’ networks in Portugal, followed by friendship networks (23.5%) and neighbourhood networks (11.9%). The less frequent type is the institutional network (2.8%), dominated by formal ties (M = 59.3%). Sociographic profiles reveal that family networks are more likely to be held by middle-old focal subjects, married or widowed, and with children. Friendship and neighbourhood networks are held by young-old subjects with different marital status, many of them living alone, with a higher proportion of men with friendship networks. Institutional networks are held by old–old, widowed or single with no children. The presented typology contributes to understand social support needs and social isolation. The conclusions allow to anticipate social services’ demand trajectories and to propose intervention plans and social policy measures to promote the well-being of the older population.